Enhancing students' aeronautical decision-making through scaffolding strategies for higher order thinking - (:unkn) unknown (My University, 2012)
Over the last few decades, classroom training in aviation education has continued mostly unchanged. It remains a highly structured presentation of information in a lecture format. The purpose of this study was to determine the effect of a method of teaching aeronautical decision making in aviation education based on integrated and scaffolded constructivist learning principles, compared to the typical structured lecture format. Although there are consistent findings in the available research literature regarding the process of integrated constructivist approaches in the classroom, few studies have focused on improving aviation student's higher order thinking by combining existing aviation concepts and tools in a cooperative learning classroom environment. Hence, this study introduced a curriculum design of explicit scaffolding of Bloom's taxonomy for higher order thinking and instructional scaffoldings for metacognition and psychological type to support learning from authentic accident cases while in cooperative groups.

The research design and assessment protocols included four scaffolding phases during a six week curriculum. National Transportation Safety Board (NTSB) accident cases in general aviation served as the educational context for the focal curriculum. The study was conducted in a classroom environment with undergraduate junior and senior aviation pilots during the first six weeks of the required course called Crew Resource Management. Pretest-posttest case study outcomes were compared between the treatments. While quantitative results did not demonstrate that the experimental condition outperformed the control condition, this study provides preliminary qualitative evidence that participants can be encouraged to think at higher levels of cognition using the revised Bloom's Taxonomy as a probing questions guide through the use of the Case Study Questionnaire to evaluate their performance as they review accident cases. The use of the instructional scaffoldings of this study supports the development of student responsibility and a student-centered cooperative classroom.

These results have implications for both practice and research. It takes time for an instructor to learn how to teach well in an authentic constructivist learning environment. Most aviation instructors today have not been provided adequate professional development training that equips them to provide instructional scaffoldings for humanizing the learning environment. The combination of tools used in this study warrant further research to heighten both the participants' and the aviation education instructors' self-awareness for improved self-management and higher order thinking skills in aeronautical decision making.

The literature in aviation has not kept pace with the vast amount of empirical research on the value of constructivist learning principles for teaching higher-order thinking skills which involves emphasizing methods and strategies for developing cognitive skills during problem solving and decision making. The aim in delivering integrated and scaffolded constructivist learning principles would be development of practices and disposition of higher order thinking that better prepare students as pilots, particularly in the context of participating with other crew members in aeronautical decision making.
Keywords: Aeronautics--Study and teaching; Thought and thinking--Study and teaching; Critical thinking--Study and teaching